Chemical constituents from Melodorum fruticosum Lour. flowers against plant pathogenic fungi - Mongkol, Rachsawan; Piapukiew, Jittra; Chavasiri, Warinthorn (Agriculture and Natural Resources, 2016)
The antifungal activity of hexane, dichloromethane and methanol extracts of 45 Thai plants were in vitro screened against plant phytopathogenic fungi (Alternaria porri, Colletotrichum gloeosporioides, Fusarium oxysporum and Phytophthora parasitica). Seven extracts strongly inhibited the mycelial growth of fungi. The plant extracts with highest antifungal activity were Limnophila aromatic, Eupatorium odoratum, Melodorum fruticosum and Alpinia galanga with 70%, 58%, 74% and 100% inhibition, respectively. The potent dichloromethane extract from M. fruticosum flowers was separated using bioassay guided against P. parasitica. Eight compounds: 1-hexacosanol (1), 5-hydroxy-7-methoxyflavone (2), b-sitosterol (3), melodorinone B (4), benzoic acid (5), chrysin (6), melodorinol (7) and melodorinone A (8) could be isolated. Among the isolated compounds, benzoic acid (5) and melodorinol (7) exhibited strong activity against mycelial growth of P. parasitica at 100% and 93% inhibition with the half maximal inhibitory concentration (IC50) values of 108 mg/mL and 130 mg/mL, respectively. This plant could be exploited for eco-friendly management control of plant diseases.